The Role of Emotional Intelligence in Employees Psychological Distress During COVID-19 Pandemic - Siti Sarawati JOHAR; Mohamad Isa AMAT (Communications of International Proceedings, 2021)
This study focuses on the influence of emotional intelligence domains on the depression, anxiety, and stress scales during the COVID-19 pandemic scenario. The specific purpose of this study was to test the effect of four emotional intelligence domains comprising the emotional intelligence of COVID-19 challenge domain based on the scales of depression, anxiety, and stress among civil servants in a statutory body in Malaysia. A total of 2268 respondents were selected for the category of academic and non-academic services. The first measurement tool used was a questionnaire survey that was developed by the researchers, and it had gone through the validity process of instrument and construct, namely, the Emotional Intelligence Domain Inventory of COVID-19 Challenge (EIDInv-CvdC). The second questionnaire is a well-established questionnaire that is the Depression, Anxiety and Stress Scales (DASS21). In this study, regression analysis was used to determine the effect between the domains of emotional intelligence on the dependent variable. The findings show that there is a significant effect in all four domains of emotional intelligence on the scales of depression, anxiety, and stress.
Keywords: Role; Emotional Intelligence; Employees; Psychological; Pandemic.